Ranas del género Pipa (Anura: Pipidae) de la Orinoquia colombiana: nuevos registros y comentarios sobre su taxonomía, distribución e historia natural (2016)
Two sympatric species of aquatic frogs (Pipa pipa and Pipa snethlageae) are reported for the first time for the Bita and Orinoco rivers in the moriche palm swamp streams of the floodplain, in the department of Vichada, Colombia. Updated maps are provided with the extension of the range of these two species, comments on their taxonomy and some aspects of their natural history are described.